An Early Crescent: The Future of Knowledge and the Environment in Islam (American Journal of Islam and Society, 1991)
An Early Crescent is about the exciting and greatly anticipated emergenceof ideas which will inaugurate the rededication and renewal of Muslim effortand spirituality. It is about the process of intellectually taking charge of theenvironment and the discourse dominated by the West. There are twodimensions to this process of taking charge. One is the Islamization ofKnowledge, and entails mastering the dominant idiom and then, from a positionof strength and confidence, creating a uniquely Islamic paradigm in the fieldof knowledge. The second dimension recognizes that “discourse” is not justacademic knowledge, but that discourse and knowledge are also inextricablytied into the environments and ecologies surrounding the Islamic community.The book is structured between the overview of Anwar Ibrahim and theepilogue of Abdullah Omar Naseef, two people deeply involved incontemporary politics, thinking, and policy making. Between this are writingsabout two dimensions of the process of taking charge of the dominant discourse,with the first part considering the Islamization of Knowledge and theepistemological characterization of the contemporary discourse, dominatedas it is by the West, and the second part dealing with the way the dominantdiscourse configures the environment and ecology surrounding everyone ingeneral, and the way it constrains the ummah specifically.Ziauddin Sardar‘s critique of the Islamization work plan centers aroundits veneer of positivism and the concommitant reification of the disciplines.Certainly there are overtones of positive theory building in the work plan,but it must also be remembered that the work plan is not designed to berevolutionary as much as corrective, and that it is aimed not so much atintellectuals as at students through the production of textbooks. And textbooksare certainly examples of knowledge-production. But no one who reads theimpassioned prose of al Faruqi can imagine that here is a man who wouldsimply pass an Islamic wand over the disciplines to Islamize them. On thecontrary, his descriptions of contemporary Muslim alienation imply that we ...